Regional Strategy Paper and Regional Indicative Programme 2008-2013 ([s.n.] [S.l.], 2008)
Presents the Regional Strategy Paper including an Indicative Programme of Community Aid in favour of the Caribbean Region which was drawn up in accordance with the provisions of Article 8 and 10 of Annex IV to the ACP-EU Partnership Agreement signed in Cotonou on 23 June 2000 as revised in Luxembourg on 28 June, 2005.
Keywords: REGIONAL INTEGRATION